3D-printing of polymer‐derived SiCN ceramic matrix composites by digital light processing. Issue 13 (October 2022) - Huang, Minzhong; Wu, Yangyang; Ou, Jun; Huang, Yao; Wang, Junye; Wu, Shanghua
Abstract: In this study, we present a DLP 3D-printing strategy for the fabrication of SiCN ceramic matrix composites (CMCs). The polysilazane-based preceramic polymer containing inert fillers was UV-cured into a green body and then converted to SiCN CMCs after pyrolysis. The introduced fillers (Si3 N4 particles and Si3 N4 whiskers) as reinforcements are well dispersed in the matrix, which can not only effectively reduce the linear shrinkage and weight loss, but also greatly improve the mechanical properties of the SiCN CMCs. The bending strength of the SiCN CMCs reinforced with 10 wt% Si3 N4 whiskers (without surface polished) reached 180.7 ± 15.6 MPa. Furthermore, the effect of fillers content on microstructure and porosity of the SiCN CMCs are discussed, and it was found that the excessive fillers led to increased pore defects and decreased continuity of the matrix, thereby reducing the mechanical properties of the SiCN CMCs. This strategy provides a promising ceramic manufacturing technique to fabricate polymer‐derived CMCs with complex-shaped and high-performance for potential demanding applications.